Sweet Offerings in Chinese Cultural Rituals in Jakarta - Bravely Satrio Wibowo; C. Dewi Hartati (Published by Confucius Institute UNS, 2025)
This article discusses sweets in Chinese traditional cultural rituals (consider to use traditional Chinese ritual). Ritual is very important because through a study of the rituals of a group, we can understand a religion. Religious action is primarily demonstrated in rituals. (add a line about why ritual is important for the Chinese life, and why did you discusses the offerings, instead of the ritual performance. Make it 2 or 3 sentence). Food is one of the centers of a ritual because food offerings is one of the pillars of Chinese culture. The research was conducted within a family in Jakarta and at the Toa Se Bio Temple in Jakarta. The research methodology used in this study is qualitative methods, with data collection through observation, interviews, documentation, and data analysis carried out in 2023. This article specifically discusses the meaning and function of sweets in three Chinese cultural rituals: the pre-wedding tradition (sangjit), the Chinese New Year ritual, and the the deity's birthday ceremony (sejit). The research results show that sweets in Chinese cultural rituals function as a means of communication to the gods and humans. Sweets also symbolize the hope that life will always be as sweet as the sweet offerings.